2018
DOI: 10.22178/pos.31-2
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Municipal Awareness as a Construct for Enhancing Citizen Satisfaction in Municipal Council of Malaysia

Abstract: Abstract. This research study critically analysed the existing literature on municipal awareness relevancy of Municipal councils' service delivery for the purpose of enhancing citizen satisfaction. The purpose of the study is the investigation of citizen satisfaction level of municipal services. Analysis of the existing literature on the relationship between municipal awareness and citizen satisfaction. The Material and methods were carried out using secondary data and were meticulously and critically analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…It is notable that the citizens’ satisfaction is linked with the awareness of users about service delivery and their expectations from the government (Bello et al, 2017). Findings of the present study show that the people viewed SUWIDHA centre more positively and felt more satisfied where literacy rate was high and familiarity with computer and e-governance practices was more.…”
Section: Punjab Experience: Observationsmentioning
confidence: 99%
“…It is notable that the citizens’ satisfaction is linked with the awareness of users about service delivery and their expectations from the government (Bello et al, 2017). Findings of the present study show that the people viewed SUWIDHA centre more positively and felt more satisfied where literacy rate was high and familiarity with computer and e-governance practices was more.…”
Section: Punjab Experience: Observationsmentioning
confidence: 99%
“…This issue might cause by their lack of awareness on the administration of local government as mention by Almarshad (2011) and the citizens responsiveness on public service delivery by their local government are determine by their level of awareness. The lack of public participation is link with the seriousness of the local government to enlighten their citizens as some of the local government have no adequate information channel to the citizens Bello et al (2017). More than 61 percent of respondents in Manjung and Kerian District stated that they did not participate in any plans or improvements in service delivery by local government and they are not aware on their right to contribute in making decision om planning and development programs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Supposedly in ideal situation, the local councils are to serve at their best in meeting citizens' needs and wants based on the power accorded by the Local Government Act 1976 (Act 171) and ensure that everyone is happy and satisfied with the councils' clear defined role and functions, effectiveness, caring, and prompt attendance on local issues. However, analysis of related literature indicates that in reality the majority of the citizens were found discontented (Bello, Martin & Kasim 2017b;Zakaria et al, 2011;Zikri, Tarmiji & Aziz, 2015), very few were revealed satisfied (Mansor & Che Mohd Razali, 2010). These were due to many reasons such as the local government is under the 'state-list' and the State has direct financial powers to appoint councillors over the local government.…”
Section: Current Research Backgroundmentioning
confidence: 99%